Transcriptomic Analysis of Quinoa Reveals a Group of Germin-Like Proteins Induced by Trichoderma - Rollano-Peñaloza, Oscar M.; Mollinedo, Patricia A.; Widell, Susanne; Rasmusson, Allan G. (Frontiers in Fungal Biology, 2021)
Symbiotic strains of fungi in the genus Trichoderma affect growth and pathogen resistance of many plant species, but the interaction is not known in molecular detail. Here we describe the transcriptomic response of two cultivars of the crop Chenopodium quinoa to axenic co-cultivation with Trichoderma harzianum BOL-12 and Trichoderma afroharzianum T22. The response of C. quinoa roots to BOL-12 and T22 in the early phases of interaction was studied by RNA sequencing and RT-qPCR verification. Interaction with the two fungal strains induced partially overlapping gene expression responses. Comparing the two plant genotypes, a broad spectrum of putative quinoa defense genes were found activated in the cultivar Kurmi but not in the Real cultivar. In cultivar Kurmi, relatively small effects were observed for classical pathogen response pathways but instead a C. quinoa-specific clade of germin-like genes were activated. Germin-like genes were found to be more rapidly induced in cultivar Kurmi as compared to Real. The same germin-like genes were found to also be upregulated systemically in the leaves. No strong correlation was observed between any of the known hormone-mediated defense response pathways and any of the quinoa-Trichoderma interactions. The differences in responses are relevant for the capabilities of applying Trichoderma agents for crop protection of different cultivars of C. quinoa.